The berry pickers eaudiobook - Peters, Amanda (Recorded Books, Inc., 2023)
A four-year-old Mi'kmaq girl goes missing from the blueberry fields of Maine, sparking a tragic mystery that haunts the survivors, unravels a family, and remains unsolved for nearly fifty years July 1962. Following in the tradition of Indigenous workers from Nova Scotia, a Mi'kmaq family arrives in Maine to pick blueberries for the summer. Weeks later, four-year-old Ruthie, the family's youngest child, vanishes. She is last seen by her six-year-old brother, Joe, sitting on a favorite rock at the edge of a berry field. Joe will remain distraught by his sister's disappearance for years to come. In Maine, a young girl named Norma grows up as the only child of an affluent family. Her father is emotionally distant, her mother frustratingly overprotective. Norma is often troubled by recurring dreams and visions that seem more like memories than imagination. As she grows older, Norma slowly comes to realize there is something her parents aren't telling her. Unwilling to abandon her intuition, she will spend decades trying to uncover this family secret. For readers of The Vanishing Half and Woman of Light, this showstopping debut by a vibrant new voice in fiction is a riveting novel about the search for truth, the shadow of trauma, and the persistence of love across time.